1995
DOI: 10.1063/1.113834
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of dielectric breakdown with hole transport for ultrathin thermal oxides and N2O oxynitrides

Abstract: In this letter, the dielectric breakdown characteristics of thermal oxides and N2O-based oxynitrides have been studied. A direct correlation was found between dielectric breakdown and the hole current generated within the gate dielectrics. The dependence of dielectric breakdown on oxide thickness was also studied. It was found that both charge-to-breakdown and hole-fluence-to-breakdown for the N2O oxynitrides were higher than those for the thermal oxides throughout the thickness range studied (33–87 Å). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Further, nitrided oxides have been reported to demonstrate some improvements in electrical properties, such as reduced interface-state generation, 1 increased resistance to hot carrier injection, 2 higher dielectric breakdown reliability, 3,4 and strong immunity against ionizing radiation. 5 On the other hand, the introduction of nitrogen causes a serious problem of negative-bias temperature instability ͑NBTI͒ in p-type MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…Further, nitrided oxides have been reported to demonstrate some improvements in electrical properties, such as reduced interface-state generation, 1 increased resistance to hot carrier injection, 2 higher dielectric breakdown reliability, 3,4 and strong immunity against ionizing radiation. 5 On the other hand, the introduction of nitrogen causes a serious problem of negative-bias temperature instability ͑NBTI͒ in p-type MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…The Si oxide films with N incorporation [1][2][3][4][5][6][7][8][9][10][11][12][13] are believed to be candidates for replacing the conventional Si oxides because they show better performances than the conventional oxides. It is indeed reported that the N-incorporated Si oxide films reduce leakage current [8], increase charge-to-breakdown value [9], and suppress boron diffusion [10]. Although it is argued that the electrical improvement is related to lower concentration of charge traps in the Si oxynitride films, the underlying physical origins remain unknown.…”
mentioning
confidence: 99%
“…The defect concentration resulting from the RTAT model decreases as the oxide thickness is reduced, as already observed. [51,52] In summary, a new model for the SILC conduction mechanism has been proposed. Calculations are in good agreement with a large amount of experimental data, thus supporting the validity of the proposed RTAT model and the assumption of electron-hole recombination at deep levels in the oxide.…”
Section: Silc Modelingmentioning
confidence: 99%